Annual Survey of Jails: Jurisdiction-Level and Jail-Level Data, 1992 ([Verlag nicht ermittelbar], 1995)
This collection provides annual data on jail populations across the nation and examines the "spillover" effect on local jails resulting from the dramatic growth in federal and state prison populations. These data permit an assessment of the demands placed on correctional resources and provide a comprehensive picture of the adult correctional system and changes that occur within the system. Information is available on the number of inmates by sex, race, adult or juvenile status, reason being held, and cause of death. Also added in the 1992 survey were variables on citizenship, population movement, and total number of inmate deaths for inmates originally confined to the facility in question who died either at that facility or elsewhere. Also, the 1992 version included a more complete survey of jail programs and a supplemental questionnaire (CJ-5S), which dealt with AIDS-related questions. In addition, information was collected for the first time on drug testing, programs that treated or educated inmates, boot camps, work release, and alternatives to incarceration such as electronic monitoring, house arrest, community service, and weekend or day reporting.